IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI JENJANG KELAS 5 SD - Siti Nurhaliza Hertiani; Mora Alifia Defahmi, Kamal Bagus Hutomo, Linailil Anam, Abdul Fadhil (CV. ADIBA AISHA AMIRA, 2025)
This paper intends to analyze the implementation of Merdeka Curriculum in Islamic Religious Education and Ethics subjects for grade 5 elementary school students. This curriculum is designed to provide a learning space that focuses on developing students' character and competencies holistically. This research uses the literature review method, including analysis of various literature, curriculum documents, and relevant studies related to the implementation of the Merdeka Curriculum in these subjects. The results of the analysis show that Merdeka Curriculum emphasizes project-based learning, strengthening the values of Pancasila students, and thematic and contextual learning approaches. However, its implementation faces several challenges, such as teacher readiness, availability of supporting facilities, and adaptation of teaching materials. Therefore, this study recommends increased efforts by educators and policymakers to ensure a more inclusive and adaptive implementation of the Merdeka Curriculum in accordance with educational goals